A review of the diabetic foot in Malaysian perspective - Abdul Hadi, Azwanis; Md Aris, Mohd Aznan; Azmi, Nurul Husna; Nasreen, Hashima E; Che Ahmad, Aminudin (Society for Advance Healthcare Research, 2019)
One of the most common complication of diabetes is the development of foot ulcer which could lead to lower limb amputation and even death. Diabetic foot causes significant impact to the patient, community and country. Therefore, detection of a diabetic foot at risk of ulceration is essential to prevent theses complications. This article will discuss regarding the diabetic foot, the factors associated with it and the variety of systems that are used for its classification, with some focus on the Malaysian perspective.